2022
DOI: 10.1101/2022.06.10.495686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial encoding of odors in the mosquito antennal lobe

Abstract: Among the cues that a mosquito uses to find a host for blood-feeding, the smell of the host plays an important role. Previous studies have shown that host odors contain hundreds of chemical odorants, which are detected by different receptors on the peripheral sensory organs of mosquitoes. But how individual odorants are encoded by downstream neurons in the mosquito brain is not known. We developed an in vivo preparation for patch-clamp electrophysiology to record from projection neurons and local neurons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 102 publications
(141 reference statements)
2
9
0
Order By: Relevance
“…We performed in vivo whole-cell patch recordings from PNs and LNs in Aedes aegypti (P. Singh et al, 2022). In our experimental preparation, we could target cell bodies in medial, dorsal, and dorsolateral regions around the AL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed in vivo whole-cell patch recordings from PNs and LNs in Aedes aegypti (P. Singh et al, 2022). In our experimental preparation, we could target cell bodies in medial, dorsal, and dorsolateral regions around the AL.…”
Section: Resultsmentioning
confidence: 99%
“…Even among I-MD3 PNs, which were more frequently activated by CO 2 among the PNs examined in our dataset, there was considerable heterogeneity in the responses (Figure 1e) : the first two PNs included in the figure showed clear excitatory responses to CO 2 , the third PN was inhibited by CO 2 , the fourth PN showed a temporally patterned response with an excitatory bout followed by an inhibitory bout, and the fifth PN showed an inhibitory bout followed by a bout of delayed excitation. Given that I-MD3 PNs primarily receive their input from the 1-octen-3-ol-sensitive sensory neurons in the capitate peg sensillum (Singh et al, 2022), it is likely that the excitatory responses to CO 2 observed in some of the I-MD3 PNs are mediated by lateral excitatory inputs within the AL. In a few PNs, we could test the responses to different concentrations of CO 2 (0.001, 0.0025, 0.005 and 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic labeling experiments have shown that cpA neurons project to I-MD1 glomerulus, while cpB and cpC project to the other two glomeruli (Herre et al 2022). Using patch-clamp recordings and post-hoc dye filling, we were able to observe the odor responses of some PNs innervating these glomeruli (Singh et al 2022). As we show below, I-MD2 PN responded strongly to 4-methylcyclohexanol but not to CO 2 or 1-octen-3-ol, while I-MD3 PNs responded to 1-octen-3-ol: thus, we inferred that cpB neurons project to I-MD2 and cpC neurons project to I-MD3 glomerulus.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the activity of a PN depends not only on the sensory input it receives from the sensory neurons, but also on the lateral inputs received from other neurons within the antennal lobe. Gammaaminobutyric acid (GABA) is one of the primary inhibitory neurotransmitters inside the Aedes brain (Matthews et al 2016), and GABA-positive LNs have been described in the antennal lobe (Singh et al 2022). Could lateral interactions also contribute to the observed plasticity in I-MD3 PNs?…”
Section: Significance Of the Cpc Plasticity To Downstream Neuronsmentioning
confidence: 99%